2015
DOI: 10.1159/000381296
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Innate Immunity in Graft-versus-Host Disease: Implications for Novel Targets?

Abstract: Acute graft-versus-host disease (GvHD) is mediated by alloreactive donor-derived T cells with a suitable T cell receptor recognizing recipient major histocompatibility complex or minor histocompatibility antigens. However, the process of T cell activation and tissue injury sensing is also dependent on innate immune cells and non-hematopoietic cells. Different cell types of the innate immune system have the ability to sense danger-associated and pathogen-associated molecular patterns via pattern recognition rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
6
0
1
Order By: Relevance
“…This allows translocation of GI flora across the mucosal barrier ( 37 , 38 ) resulting in the release of inflammatory cytokines ( 39 ), danger associated molecular patterns (DAMPs), and pathogen associated molecular patterns (PAMPs). These molecules are then recognized by PRRs on APCs, allowing for their activation ( 40 42 ).…”
Section: Tlrs In Agvhdmentioning
confidence: 99%
“…This allows translocation of GI flora across the mucosal barrier ( 37 , 38 ) resulting in the release of inflammatory cytokines ( 39 ), danger associated molecular patterns (DAMPs), and pathogen associated molecular patterns (PAMPs). These molecules are then recognized by PRRs on APCs, allowing for their activation ( 40 42 ).…”
Section: Tlrs In Agvhdmentioning
confidence: 99%
“…Emerging data showed that donor TLR4 and MyD88 deficiencies are protective against aGVHD [48], while activation of TLR9 with CpG-ODN in recipients markedly accelerates GVHD lethality [38,39]. Hence, novel therapeutic strategies that target TLR-mediated signaling pathways may be able to reduce the occurrence and severity of GVHD [49]. …”
Section: Inhibition Of Tlr Signaling Pathwaysmentioning
confidence: 99%
“…NETs are identified as a new defensive mechanism of neutrophils against infectious pathogens through delivering a high local concentration of antimicrobial agents, such as myeloperoxidase (MPO) and neutrophil elastase (NE) [3]. Given the role of innate immune cells in the pathogenesis of graft versus host disease (GVHD) [4,5], whether NETs are involved in GVHD remains unclear. In this study, we aimed to evaluate surrogate parameters of NETs formation in patients with acute GVHD (aGVHD).…”
Section: Dear Editormentioning
confidence: 99%